Conflitos na educação: potência para construção de uma cultura de paz ou manutenção da cultura da violência - Santos, Rafaela Cordeiro dos (2023)
This research aimed to investigate the conceptions and practices of social educators in the management of conflicts in educational spaces and the articulation with the construction of a culture of peace or maintenance of a culture of violence. The investigation had socioeducational and physical-sports programs aimed at children, adolescents and young people from Sesc-SP (Social Service of Commerce of the State of São Paulo), namely: Curumim, Juventudes and Sesc Sports Program. The methodology used is a qualitative approach, consisting of bibliographical study, document analysis and field research. Data collection was carried out through interviews with educators from these programs, which allowed understanding the practices and challenges faced by educators in socio-educational actions in the face of conflicts. The research also made it possible to record practices related to the culture of peace and non-violence carried out in Sesc-SP Programs, as a non-formal education space committed to comprehensive education, people's emancipation and social transformation. The theoretical foundations are based on concepts such as education, curriculum, violence, conflict, culture of peace and culture of violence. This context is articulated with the hypothesis that educators face difficulties in managing the conflicts that emerge during their pedagogical practices and due to the lack of training consistent with this educational reality. Data analysis includes reflections on the high incidence of conflicts in educational practices with children and adolescents and the difficulties faced by educators in managing these conflicts. The research results also express the need to review the conception of educator training, in view of the articulation of conflict management with the promotion of a culture of peace and non-violence in socio-educational spaces